2013
DOI: 10.1371/journal.pone.0060041
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Function in Acromegaly after Surgical Resection of GH-Secreting Adenoma versus Naïve Acromegaly

Abstract: Patients with active untreated acromegaly show mild to moderate neurocognitive disorders that are associated to chronic exposure to growth hormone (GH) and insulin-like growth factor (IGF-I) hypersecretion. However, it is unknown whether these disorders improve after controlling GH/IGF-I hypersecretion. The aim of this study was to compare neurocognitive functions of patients who successfully underwent GH-secreting adenoma transsphenoidal surgery (cured patients) with patients with naive acromegaly. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…An irreversible effect of excess GH on cognitive functioning cannot be excluded (26), but future studies should also focus on various interventions, both psychological and cosmetic, to assess the impact of such strategies on improving psychopathological outcomes.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…An irreversible effect of excess GH on cognitive functioning cannot be excluded (26), but future studies should also focus on various interventions, both psychological and cosmetic, to assess the impact of such strategies on improving psychopathological outcomes.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…At present, the number of reported patients that underwent neuropsychological evaluation after being considered adequately treated for acromegaly is still limited. Most studies evaluating cognitive function found worse scores on memory and executive functioning both in patients treated for acromegaly and for non-functioning adenomas, when compared to controls [10][11][12][13][14]. In the cohort of patients successfully treated for acromegaly at our center, cognitive function did not differ between acromegaly patients and matched controls or between acromegaly patients and patients treated for non-functioning adenomas [15].…”
mentioning
confidence: 69%
“…The clinical burden of acromegaly is further compounded by the substantial impairment in quality of life (QoL) (Rowles et al 2005, Trepp et al 2005, T'Sjoen et al 2007. Additionally, patients with acromegaly may experience neurocognitive (Leon-Carrion et al 2010, Martin-Rodriguez et al 2013) and neuropsychiatric dysfunctions (Sievers et al 2009a,b).…”
Section: Acromegaly: Backgroundmentioning
confidence: 99%
“…Indeed, in some patients, cognitive (Martin-Rodriguez et al 2013) and psychosocial (Biermasz et al 2004, van der Klaauw et al 2008) impairment may be irreversible. Despite the urgency to diagnose and treat, many patients with acromegaly still have uncontrolled disease, and there may be many more undiagnosed (Katznelson et al 2011).…”
Section: Acromegaly: Backgroundmentioning
confidence: 99%